Формування системи відтворення основних засобів промислового підприємства - Ротанов, Г. М.; Rotanov, G. (КНТУ, 2013)
У статті розроблено методичні положення щодо регулювання процесів відтворення основних засобів та використання регресивних методів нарахування амортизаційних відрахувань на промислових підприємствах. The methodical positions on regulating the fixed assets reproduction processes and usage of regressive methods of depreciation charges at the industrial enterprises are developed. Proposed approaches should enhance the economic, technical, and organizational levels of industrial enterprises, reduce their dependence on unstable external sources of financing by strengthening the role of amortization in the fixed assets renewal process. The article also analyzes the existing approaches of the fixed assets elements optimal operation timing determination. The expediency of determining the optimal operation timing, depending on management system development conditions within certain limits, is set. The article contains a definition of the fixed assets resumption features, which are in the lagging of their resumption in the natural form from the resumption of the cost, which theoretically allows making an extended resumption of utility unit at the expense of a sinking fund.
The formation of system of reproduction of the basic means of the industrial enterprise
Keywords: система; відтворення; основні засоби; промисловість; підприємство; економіка; інвестиційні ресурси; system; reproduction; basic means; industry; enterprise; economy; investment resources